Bacterial DNA findings in ruptured and unruptured intracranial aneurysms. (18th May 2016) - Pyysalo, Mikko J.; Pyysalo, Liisa M.; Pessi, Tanja; Karhunen, Pekka J.; Lehtimäki, Terho; Oksala, Niku; Öhman, Juha E.
Abstract: Objective Chronic inflammation has earlier been detected in ruptured intracranial aneurysms. A previous study detected both dental bacterial DNA and bacterial-driven inflammation in ruptured intracranial aneurysm walls. The aim of this study was to compare the presence of oral and pharyngeal bacterial DNA in ruptured and unruptured intracranial aneurysms. The hypothesis was that oral bacterial DNA findings would be more common and the amount of bacterial DNA would be higher in ruptured aneurysm walls than in unruptured aneurysm walls.Materials and methods A total of 70 ruptured ( n  = 42) and unruptured ( n  = 28) intracranial aneurysm specimens were obtained perioperatively in aneurysm clipping operations. Aneurysmal sac tissue was analysed using a real-time quantitative polymerase chain reaction to detect bacterial DNA from several oral species. Both histologically non-atherosclerotic healthy vessel wall obtained from cardiac by-pass operations (LITA) and arterial blood samples obtained from each aneurysm patient were used as control samples.Results Bacterial DNA was detected in 49/70 (70%) of the specimens. A total of 29/42 (69%) of the ruptured and 20/28 (71%) of the unruptured aneurysm samples contained bacterial DNA of oral origin. Both ruptured and unruptured aneurysm tissue samples contained significantly more bacterial DNA than the LITA control samples ( p -values 0.003 and 0.001, respectively). There was no significant difference in the amount of bacterial DNA between the ruptured and unruptured samples.Conclusion Dental bacterial DNA can be found using a quantitative polymerase chain reaction in both ruptured and unruptured aneurysm walls, suggesting that bacterial DNA plays a role in the pathogenesis of cerebral aneurysms in general, rather than only in ruptured aneurysms.